Snapshot isolation and isolation history challenge the analogy between mountains and islands used to understand endemism - Suzette G. A. Flantua; Davnah Payne; Michael K. Borregaard; Carl Beierkuhnlein; Manuel J. Steinbauer; Stefan Dullinger; Franz Essl; Severin D. H. Irl; David Kienle; Holger Kreft; Bernd Lenzner; Sietze J. Norder; et al. (Global Ecology and Biogeography, 2020)
Aim Mountains and islands are both well known for their high endemism. To explain this similarity, parallels have been drawn between the insularity of “true islands” (land surrounded by water) and the isolation of habitats within mountains (so‐called “mountain islands”). However, parallels rarely go much beyond the observation that mountaintops are isolated from one another, as are true islands. Here, we challenge the analogy between mountains and true islands by re‐evaluating the literature, focusing on isolation (the prime mechanism underlying species endemism by restricting gene flow) from a dynamic perspective over space and time. Framework We base our conceptualization of “isolation” on the arguments that no biological system is completely isolated; instead, isolation has multiple spatial and temporal dimensions relating to biological and environmental processes. We distinguish four key dimensions of isolation: (a) environmental difference from surroundings; (b) geographical distance to equivalent environment [points (a) and (b) are combined as “snapshot isolation”]; (c) continuity of isolation in space and time; and (d) total time over which isolation has been present [points (c) and (d) are combined as “isolation history”]. We evaluate the importance of each dimension in different types of mountains and true islands, demonstrating that substantial differences exist in the nature of isolation between and within each type. In particular, different types differ in their initial isolation and in the dynamic trajectories they follow, with distinct phases of varying isolation that interact with species traits over time to form present‐day patterns of endemism. Conclusions Our spatio‐temporal definition of isolation suggests that the analogy between true islands and mountain islands masks important variation of isolation over long time‐scales. Our understanding of endemism in isolated systems can be greatly enriched if the dynamic spatio‐temporal dimensions of isolation enter models as explanatory variables and if these models account for the trajectories of the history of a system.

Resistance is futile: RNA-sequencing reveals differing responses to bat fungal pathogen in Nearctic Myotis lucifugus and Palearctic Myotis myotis - Thomas M. Lilley; Jenni M. Prokkola; Anna S. Blomberg; Steve Paterson; Joseph S. Johnson; Gregory G. Turner; Tomáš Bartonička; Erik Bachorec; DeeAnn M. Reeder; Kenneth A. Field (Oecologia, 2019)
Resistance and tolerance allow organisms to cope with potentially life-threatening pathogens. Recently introduced pathogens initially induce resistance responses, but natural selection favors the development of tolerance, allowing for a commensal relationship to evolve. Mycosis by Pseudogymnoascus destructans , causing white-nose syndrome (WNS) in Nearctic hibernating bats, has resulted in population declines since 2006. The pathogen, which spread from Europe, has infected species of Palearctic Myotis for a longer period. We compared ecologically relevant responses to the fungal infection in the susceptible Nearctic M. lucifugus and less susceptible Palearctic M. myotis , to uncover factors contributing to survival differences in the two species. Samples were collected from euthermic bats during arousal from hibernation, a naturally occurring phenomenon, during which transcriptional responses are activated. We compared the whole-transcriptome responses in wild bats infected with P. destructans hibernating in their natural habitat. Our results show dramatically different local transcriptional responses to the pathogen between uninfected and infected samples from the two species. Whereas we found 1526 significantly upregulated or downregulated transcripts in infected M. lucifugus , only one transcript was downregulated in M. myotis . The upregulated response pathways in M. lucifugus include immune cell activation and migration, and inflammatory pathways, indicative of an unsuccessful attempt to resist the infection. In contrast, M. myotis appears to tolerate P. destructans infection by not activating a transcriptional response. These host-microbe interactions determine pathology, contributing to WNS susceptibility, or commensalism, promoting tolerance to fungal colonization during hibernation that favors survival. Graphic abstract

Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Distribution of Anthocyanins Delivered from a Bioadhesive Black Raspberry Gel Following Topical Intraoral Application in Normal Healthy Volunteers - Carlos M. Ugalde; Zhongfa Liu; Chen Ren; Kenneth K. Chan; Kapila A. Rodrigo; Yhonghua Ling; Peter E. Larsen; Guillermo E. Chacon; Gary D. Stoner; Russell J. Mumper; Henry W. Fields; Susan R. Mallery (Pharmaceutical Research, 2009)